2014
DOI: 10.1097/gme.0b013e3182966fd3
|View full text |Cite
|
Sign up to set email alerts
|

Combination treatment with Fructus Ligustri Lucidi and Puerariae radix offsets their independent actions on bone and mineral metabolism in ovariectomized rats

Abstract: The combination of these two herbs offsets their independent actions on bone and mineral metabolism in vivo. The results of the present study could provide insights to medical professionals to further their understanding of the potential negative impact of herb-herb interactions when a combination of herbal mixtures is used for the management of osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Meanwhile, FLL has the ability of improving liver and kidney deficiencies and reducing lower back soreness. Thusly, FLL can be clinically used to treat osteoporosis in prescriptions containing other herbs, such as Herbal Epimedii [ 21 ], Fructus Psoraleae [ 22 ], Herba Ecliptae [ 23 ] and Puerariae radix [ 24 , 25 , 26 ].…”
Section: The Bone-protective Actions Of Fructus Ligustrimentioning
confidence: 99%
“…Meanwhile, FLL has the ability of improving liver and kidney deficiencies and reducing lower back soreness. Thusly, FLL can be clinically used to treat osteoporosis in prescriptions containing other herbs, such as Herbal Epimedii [ 21 ], Fructus Psoraleae [ 22 ], Herba Ecliptae [ 23 ] and Puerariae radix [ 24 , 25 , 26 ].…”
Section: The Bone-protective Actions Of Fructus Ligustrimentioning
confidence: 99%
“…The main component of this preparation is also epimedium, which produces an anti‐osteoporosis effect in postmenopausal women mainly by reducing the concentrations of bone resorption marker and maintaining concentrations of bone formation marker. Furthermore, the effects of individual treatments such as WBV or other herbal Fufang preparations have also been extensively studied. However, there are no published studies investigating the effect of WBV combined with herbal Fufang on bone metabolism in OVX rats.…”
Section: Discussionmentioning
confidence: 99%
“…The OVX only and Sham groups received normal saline. Rats in the OVX + WBV and OVX + WBV + BZG groups underwent WBV, which was performed using an experimental vibration platform (Juvent 1000, Juvent Medical, Somerset, NJ, USA) set at a frequency of [30][31][32][33][34][35] Hz and an acceleration of 0.3 g twice a day for 20 min with a 5 min rest at the mid-point (10 mins on, 5 mins off, 10 mins on) for 5 days/week for 12 weeks [16][17][18][19] . The parameters above were confirmed by the Guangdong Medical Devices Quality Surveillance and Test Institute (NO: JK083007).…”
Section: Experimental Designmentioning
confidence: 99%
“…In the clinical TCM practice, FLL is a component among kidney-tonifying herbal formulae for the treatment of osteoporosis (Sun et al, 2008;Zhang et al, 2008a;Siu et al, 2013). Our previous study revealed that the crude extract of FLL could improve calcium balance by regulating transcellular calcium absorption in intestine and reabsorption in kidney (Zhang et al, 2006(Zhang et al, , 2008b(Zhang et al, , 2008c, consequently exerting bone-sparing function in aged female rats and aged osteoporotic rats with estrogen deficiency (Zhang et al, 2008d;Dong et al, 2014). In addition, the in vitro results demonstrated that FLL extract was able to directly promote osteogenesis (Li et al, 2010), and that the serum from rats administered with FLL could inhibit the proliferation and the differentiation of osteoclasts (Zhang et al, 2008a).…”
Section: Introductionmentioning
confidence: 98%